Batak Cultural Change in Ngeri-ngeri Sedap Movie: Robert N Entman Framing Analysis - Ega Damayanti; Handriyotopo; Aris Setiawan (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
This research aims to reveal the changes in Batak culture in the movie Ngeri-ngeri Sedap. Ngeri-ngeri Sedap is a family-drama film with a Batak ethnic background, conveying the unrest of overseas children who are bound by customs and culture. The method used in this research is media text analysis with a critical approach. The theory used is Robert N ENtman’s framing analysis theory, which analyses using the scalpel of issue selection framing and issue highlighting. The selection of issues that will be highlighted in this film is the change in Batak culture. The results of the study show that in the film Ngeri-ngeri Sedap the three sons of Mr and Mrs Domu experience cultural changes because they migrate or do not live in their area. The changes in Batak culture that occur in the film Ngeri-ngeri Sedap are: the first son Domu, did not marry a fellow Batak tribe, Sahat the last son, did not live at home and preferred to migrate away from his parents, and Sahat also began to forget the designation of the Batak family or can be called Bertutur culture.